Acne fulminans treatment: case report and literature review - Woźna, Julia; Korecka, Katarzyna; Stępka, Jan; Bałoniak, Andrzej; Żaba, Ryszard; Schwartz, Robert A. (Frontiers in Medicine, 2024)
Acne fulminans (AF), a severe acne variant primarily evident in adolescent males, is characterized by the sudden onset of severe and often ulcerating acne with fever and polyarthritis. A case of a 14-year-old initially treated with clindamycin and surgical debridement, highlights the complexity of AF, including challenges in diagnosis, treatment, and the importance of early dermatological consultation. Successful management was achieved through systemic therapy with retinoids and corticosteroids, resulting in significant improvement. This case underscores the necessity of a coordinated effort among dermatologists, endocrinologists, and rheumatologists for effective AF treatment, illustrating the critical role of timely diagnosis and comprehensive care in managing this rare and challenging condition.